Determinants of Asean Fishery Trade (A Gravity Model Approach) - Putra Irwandi; Aulia Adetya; Ninda Novita (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Indonesia is known as an archipelagic country with vast marine potential. International trade has been a key driver of rapid economic growth. Economic integration among ASEAN countries has brought significant benefits, particularly in the fishery products sector. This study aims to analyze the factors influencing the flow of fishery trade among ASEAN countries. The total number of data observations is 100, with the central destination countries including Malaysia, Singapore, Vietnam, Thailand, the Philippines, East Timor, Brunei Darussalam, Cambodia, Myanmar, and Laos. The research employs panel data from ASEAN member states covering the period from 2003 to 2022, including variables such as each ASEAN country's GDP, GDP per capita, population, exchange rates, and economic distance. The analysis is conducted using the gravity model approach, with the Random Effects Model (REM) applied to process the data. The findings reveal that the exchange rate has a positive and significant effect on fishery trade flows among ASEAN countries. This suggests that currency fluctuations play a key role in facilitating trade. Conversely, economic distance has a negative and significant effect, indicating that greater geographical and economic gaps between countries hinder the volume of fishery trade. However, other variables, such as GDP, GDP per capita, and population, do not exhibit a statistically significant impact on fishery trade flows. These results underscore the importance of exchange rates and geographical proximity in shaping trade patterns within the ASEAN fishery sector. The study provides empirical evidence that while macroeconomic indicators such as GDP and population size are often considered critical in trade analysis, their influence on fishery trade flows among ASEAN countries is limited. Understanding the role of these factors is essential for evaluating trade dynamics and addressing challenges in regional fishery trade.